Pengaruh Capital Adequacy Ratio (CAR), Loan To Deposit Ratio (LDR), Non Performing Loan (NPL), and Net Interest Margin (NIM) terhadap Perubahan Laba: (Studi Empiris Pada Perusahaan Perbankan yang Terdaftar di BEI) - Putri, Rita Dwi (Jurusan PIPS FKIP UMMY Solok, 2017)
The study population was banking company listed on the Stock Exchange Year 2009-2014 as many as 39 companies. Sampling was done by sampling method and aim (purposive sampling) which is a technique of using a particular technique for sampling considerations. Data were analyzed using multiple linear regression model. Partial test results can be concluded that the LDR and NPL has an influence on changes in earnings. It can be seen from the value t count> t table so that the H2 and H3 accepted. CAR not significant effect on changes in earnings, while NIM has no influence on changes in earnings. Can be seen from t <t table then H1 and H4 is rejected. The level of the coefficient of determination which is owned by R2 = 0.233. This means that approximately 23.3% change in bank profits is affected by variable capital adequacy ratio (CAR), the loan to deposit ratio (LDR), non-performing loan (NPL), and the net interest margin (NIM) to changes in income. While about 76.7% influenced by other variables.